Sealing resin sheet

The introduction of a hollow ceramic filler in the sealing resin sheet for semiconductor packages addresses the issue of dielectric constant reduction and transmission loss by maintaining structural integrity during the pressing process, resulting in efficient and reliable semiconductor package manufacturing.

JP7649169B2Active Publication Date: 2025-03-19NITTO DENKO CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021039163
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-11
Publication Date
2025-03-19
Estimated Expiration
2041-03-11

AI Technical Summary

Technical Problem

Existing resin compositions for semiconductor packages, which contain hollow silica to reduce the dielectric constant of the cured resin portion, face issues with hollow silica collapse during the pressing process, leading to ineffective reduction of the dielectric constant and increased transmission loss in wireless communication.

Method used

A sealing resin sheet containing a thermosetting resin and an inorganic filler, where the inorganic filler includes a hollow ceramic filler, such as aluminoborosilicate glass, which maintains its structure during the pressing process and effectively reduces the dielectric constant of the cured resin portion.

Benefits of technology

The use of a hollow ceramic filler in the sealing resin sheet allows for the formation of a cured resin portion with a low dielectric constant, thereby reducing transmission losses in wireless communication while maintaining the occupied volume of the filler, ensuring efficient manufacturing of semiconductor packages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649169000002
    Figure 0007649169000002
  • Figure 0007649169000003
    Figure 0007649169000003
  • Figure 0007649169000001
    Figure 0007649169000001
Patent Text Reader

Abstract

To provide a resin sheet for sealing which is suitable for efficiently manufacturing a semiconductor package that suppresses transmission loss of radio communication.SOLUTION: A resin sheet X for sealing contains a thermosetting resin and an inorganic filler. The inorganic filler contains a hollow ceramic filler.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an encapsulating resin sheet. [Background technology]

[0002] In the manufacturing process of a semiconductor package, after a semiconductor chip is mounted on a substrate such as a mounting board, a cured resin portion that covers the semiconductor chip is formed to seal the semiconductor chip. A sheet-shaped resin composition (resin sheet) is known as an encapsulating resin composition for forming a cured resin portion. With the resin sheet, the semiconductor chip is encapsulated, for example, through the following pressing process and curing process. In the pressing process, the resin sheet is softened by heating and pressed toward the substrate in a state where the resin sheet is in contact with a plurality of semiconductor chips arranged on the substrate. As a result, each semiconductor chip on the substrate is covered with the resin sheet. In the curing process, the resin sheet that covers the semiconductor chip is cured by further heating. As a result, a cured resin portion is formed around each semiconductor chip on the substrate, and each semiconductor chip is encapsulated. Technology related to resin encapsulation of semiconductor chips is described, for example, in Patent Document 1 below.

[0003] On the other hand, in a semiconductor package having a wireless communication function, it is known that the transmission loss when a radio signal transmitted and received by a semiconductor chip passes through a cured resin portion is proportional to the relative dielectric constant of the cured resin portion and the signal frequency. In such a semiconductor package, in order to reduce the transmission loss, it is required that the dielectric constant of the cured resin portion around the semiconductor chip is small. The higher the operating frequency of the semiconductor chip, the stronger this requirement becomes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-80327 A Summary of the Invention [Problem to be solved by the invention]

[0005] In order to reduce the dielectric constant of the cured resin portion, hollow silica is blended into the resin composition described in Patent Document 1. However, hollow silica is easily crushed in the above-mentioned pressing process. Therefore, the resin composition of Patent Document 1 cannot effectively reduce the dielectric constant of the cured resin portion. Such a resin composition is not preferable from the viewpoint of suppressing transmission loss.

[0006] The present invention provides an encapsulating resin sheet suitable for efficiently manufacturing a semiconductor package in which transmission loss in wireless communication is suppressed. [Means for solving the problem]

[0007] The present invention [1] relates to a sealing resin sheet containing a thermosetting resin and an inorganic filler, the inorganic filler including a hollow ceramic filler.

[0008] As described above, the sealing resin sheet of the present invention contains a hollow ceramic filler as an inorganic filler. A ceramic filler having a hollow structure has a smaller dielectric constant per occupied volume than a ceramic filler having a solid structure. In addition, the hollow ceramic filler is hard and is not easily crushed in the above-mentioned pressing process. A sealing resin sheet containing such a hollow ceramic filler is suitable for effectively forming a cured resin part with a low dielectric constant while suppressing a decrease in the occupied volume of the hollow inorganic filler in the above-mentioned pressing process. Such a sealing resin sheet is suitable for collectively sealing a plurality of semiconductor chips with a cured resin part with a low dielectric constant, and is therefore suitable for efficiently manufacturing a semiconductor package in which the transmission loss of wireless communication is suppressed.

[0009] The present invention [2] includes the sealing resin sheet according to the above [1], in which the content of the hollow ceramic filler is 50 volume % or more.

[0010] Such a configuration is preferable for lowering the dielectric constant of the cured resin portion formed from the sealing resin sheet.

[0011] The present invention [3] includes the sealing resin sheet according to the above [1] or [2], in which the content of the hollow ceramic filler is 85 vol % or less.

[0012] Such a configuration is preferable for avoiding excessive thickening of the encapsulating resin sheet and ensuring the flowability of the encapsulating resin sheet in the above-mentioned pressing step.

[0013] The present invention [4] includes the encapsulating resin sheet according to any one of the above [1] to [3], which has an average linear thermal expansion coefficient of 50 ppm / ° C. or less at 30° C. to 50° C. after curing.

[0014] Such a configuration is suitable for preventing the above-mentioned hardened resin portion from peeling off from the semiconductor chip, and is therefore preferable for ensuring sealing reliability.

[0015] The present invention [5] includes the encapsulating resin sheet according to any one of the above [1] to [4], which has a tensile storage modulus at 25° C. after curing of 1 GPa or more.

[0016] Such a configuration is preferable for ensuring the strength of the cured resin portion described above.

[0017] The present invention [6] includes the encapsulating resin sheet according to any one of the above [1] to [5], which has a relative dielectric constant of 3.4 or less at 10 GHz after curing.

[0018] Such a configuration is preferable for reducing the transmission loss of high-frequency signals passing through the cured resin portion. [Brief description of the drawings]

[0019] [Figure 1] 1 is a schematic cross-sectional view of an embodiment of an encapsulating resin sheet of the present invention. FIG. [Diagram 2]2 shows an example of a method of using the encapsulating resin sheet shown in Fig. 1. Fig. 2A shows a process of placing a workpiece and an encapsulating resin sheet between press plates of a flat press machine, Fig. 2B shows a pressing process, and Fig. 2C shows a curing process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] As shown in FIG. 1, an encapsulating resin sheet X as one embodiment of the encapsulating resin sheet of the present invention extends in a direction perpendicular to the thickness direction T. The encapsulating resin sheet X is a sheet-formed product of a thermosetting composition for forming a cured resin part for encapsulating a semiconductor chip. The encapsulating resin sheet X is preferably a sheet-formed product of a thermosetting composition for forming a cured resin part for encapsulating a semiconductor chip for wireless communication. The thermosetting composition contains a thermosetting resin and an inorganic filler. That is, the encapsulating resin sheet X is formed from a thermosetting composition and contains a thermosetting resin and an inorganic filler. The encapsulating resin sheet X is in a semi-cured state (B-stage state).

[0021] Examples of the thermosetting resin include epoxy resin, silicone resin, urethane resin, polyimide resin, urea resin, melamine resin, and unsaturated polyester resin. These thermosetting resins may be used alone or in combination of two or more. The content of the thermosetting resin in the thermosetting composition is preferably 3% by mass or more, more preferably 3.5% by mass or more. The content of the thermosetting resin in the thermosetting composition is preferably 35% by mass or less, more preferably 30% by mass or less.

[0022] The thermosetting resin preferably contains an epoxy resin. Examples of the epoxy resin include bifunctional epoxy resins and trifunctional or higher polyfunctional epoxy resins. Examples of the bifunctional epoxy resin include bisphenol A type epoxy resins, bisphenol F type epoxy resins, modified bisphenol A type epoxy resins, modified bisphenol F type epoxy resins, and biphenyl type epoxy resins. Examples of the trifunctional or higher polyfunctional epoxy resins include phenol novolac type epoxy resins, cresol novolac type epoxy resins, trishydroxyphenylmethane type epoxy resins, tetraphenylolethane type epoxy resins, and dicyclopentadiene type epoxy resins. These epoxy resins may be used alone or in combination of two or more. As the epoxy resin, a bifunctional epoxy resin is preferably used, and more preferably a bisphenol F type epoxy is used.

[0023] The epoxy equivalent of the epoxy resin is preferably 10 g / eq or more, more preferably 50 g / eq or more, and even more preferably 100 g / eq or more. The epoxy equivalent of the epoxy resin is preferably 500 g / eq or less, more preferably 450 g / eq or less, and even more preferably 400 g / eq or less. When the thermosetting resin contains multiple epoxy resins, the epoxy equivalent is the weighted average epoxy equivalent of the multiple epoxy resins.

[0024] When an epoxy resin is used, the thermosetting resin preferably contains a phenolic resin as a curing agent for the epoxy resin. Such a configuration is suitable for the encapsulating resin sheet X to exhibit high heat resistance and high chemical resistance after curing, and is therefore suitable for forming a cured resin part with excellent encapsulation reliability from the encapsulating resin sheet X. As the phenolic resin, a novolac type phenolic resin is preferably used. Examples of the novolac type phenolic resin include phenol novolac resin, phenol aralkyl resin, trishydroxyphenylmethane novolac resin, cresol novolac resin, tert-butylphenol novolac resin, and nonylphenol novolac resin. These phenolic resins may be used alone or in combination of two or more kinds.

[0025] In the thermosetting composition, the amount of hydroxyl groups in the phenolic resin relative to 1 equivalent of the epoxy group of the epoxy resin is preferably 0.7 equivalents or more, more preferably 0.9 equivalents or more. In the thermosetting composition, the amount of hydroxyl groups in the phenolic resin relative to 1 equivalent of the epoxy group of the epoxy resin is preferably 1.5 equivalents or less, more preferably 1.2 equivalents or less. In addition, the amount of the phenolic resin to be blended relative to 100 parts by mass of the epoxy resin is preferably 20 parts by mass or more, more preferably 30 parts by mass or more. The amount of the phenolic resin to be blended as a curing agent relative to 100 parts by mass of the epoxy resin is preferably 80 parts by mass or less, more preferably 70 parts by mass or less.

[0026] The inorganic filler includes a ceramic filler having a hollow structure (hollow ceramic filler). The hollow ceramic filler is a hollow filler made of a sintered inorganic material. Examples of the material of the hollow ceramic filler include oxide ceramics, nitride ceramics, carbide ceramics, and glass ceramics. Examples of the oxide ceramics include titanium oxide, aluminum oxide, zirconium oxide, and cesium oxide. Examples of the nitride ceramics include silicon nitride, titanium nitride, and aluminum nitride. Examples of the carbide ceramics include silicon carbide, titanium carbide, and tungsten carbide. Examples of the glass ceramics include aluminoborosilicate glass, aluminoborosilicate glass, lead borosilicate glass, and zinc borosilicate glass. As the hollow ceramic filler, glass ceramics are preferably used, and more preferably aluminoborosilicate glass is used.

[0027] The average particle diameter of the hollow ceramic filler is preferably 0.1 μm or more, more preferably 0.5 μm or more. The average particle diameter is preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. These configurations are preferable for ensuring good viscosity in the sealing resin sheet X and ensuring chip shape conformability in the pressing process described below. The average particle diameter of the hollow ceramic filler is the median diameter in the volume-based particle size distribution (the particle diameter at which the volume cumulative frequency reaches 50% from the small diameter side), and is determined based on the particle size distribution obtained by, for example, a laser diffraction / scattering method (the same applies to the average particle diameters of other inorganic fillers).

[0028] The particle density of the hollow ceramic filler is preferably 0.3 g / cm 3 More preferably, 0.5 g / cm 3 More preferably, it is 0.9 g / cm 3 Less than or equal to 0.8 g / cm 3Such a configuration is preferable for lowering the dielectric constant of the cured resin portion described above, and is therefore preferable for reducing the transmission loss of high frequency signals passing through the cured resin portion.

[0029] The content of the hollow ceramic filler in the thermosetting composition is preferably 15% by volume or more, more preferably 50% by volume or more, even more preferably 60% by volume or more, even more preferably 65% ​​by volume or more, especially more preferably 70% by volume or more, and particularly preferably 75% by volume or more. The content of the hollow ceramic filler in the inorganic filler is preferably 20% by volume or more, more preferably 50% by volume or more, even more preferably 80% by volume or more, and particularly preferably 100% by volume. These configurations are preferable for lowering the dielectric constant of the cured resin portion formed from the sealing resin sheet X. In addition, the content of the hollow ceramic filler in the thermosetting composition is preferably 85% by volume or less, more preferably 82% by volume or less, and even more preferably 80% by volume or less. Such a configuration is preferable for avoiding excessive thickening of the sealing resin sheet X and ensuring the fluidity of the sealing resin sheet X in the pressing process described below.

[0030] The inorganic filler may contain an inorganic filler (other inorganic filler) other than the hollow ceramic filler. Examples of the other inorganic filler include inorganic particles having a solid structure (solid inorganic particles). Examples of the material of the solid inorganic particles include silica, calcium oxide, magnesium oxide, titanium oxide, aluminum oxide, zirconium oxide, cesium oxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, aluminum nitride, boron nitride, silicon nitride, and silicon carbide. The solid inorganic particles may be used alone or in combination of two or more kinds. As the solid inorganic particles, solid silica particles are preferably used.

[0031] The solid inorganic particles have an average particle size of preferably 0.1 μm or more, more preferably 0.5 μm or more. The average particle size is preferably 20 μm or less, more preferably 10 μm or less. These configurations are preferable for ensuring good viscosity in the sealing resin sheet X and ensuring the chip shape conformability in the pressing process described later.

[0032] The content of the solid inorganic particles in the thermosetting composition is preferably 70% by volume or less, more preferably 65% ​​by volume or less, and even more preferably 60% by volume or less. The content of the solid inorganic particles in the inorganic filler is preferably 80% by volume or less, more preferably 50% by volume or less, even more preferably 20% by volume or less, and particularly preferably 0% by volume. These configurations are preferable for ensuring the flowability of the sealing resin sheet X.

[0033] The content of the inorganic filler including the hollow ceramic filler in the thermosetting composition is preferably 15% by volume or more, more preferably 50% by volume or more, even more preferably 60% by volume or more, even more preferably 65% ​​by volume or more, especially preferably 70% by volume or more, and particularly preferably 75% by volume or more. The content is preferably 85% by volume or less, more preferably 82% by volume or less, and even more preferably 80% by volume or less. These configurations are preferable for achieving both the above-mentioned fluidity of the sealing resin sheet X and the above-mentioned low dielectric constant of the cured resin part.

[0034] The thermosetting composition may contain other components, such as a curing accelerator, a thermoplastic resin, a pigment, and a silane coupling agent.

[0035] The curing accelerator is a catalyst (thermosetting catalyst) that accelerates the curing of a thermosetting resin by heating. Examples of the curing accelerator include imidazole compounds and organic phosphorus compounds. Examples of the imidazole compounds include 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Examples of the organic phosphorus compounds include triphenylphosphine, tricyclohexylphosphine, tributylphosphine, and methyldiphenylphosphine. As the curing accelerator, an imidazole compound is preferably used, and more preferably 2-phenyl-4,5-dihydroxymethylimidazole is used. The amount of the curing accelerator to be blended relative to 100 parts by mass of the thermosetting resin is, for example, 0.05 parts by mass or more, and, for example, 5 parts by mass or less.

[0036] Examples of thermoplastic resins include acrylic resins, natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, polybutadiene resins, polycarbonate resins, thermoplastic polyimide resins, polyamide resins, phenoxy resins, saturated polyester resins (PET, etc.), polyamideimide resins, fluororesins, and styrene-isobutylene-styrene block copolymers. These thermoplastic resins may be used alone or in combination of two or more.

[0037] As the thermoplastic resin, from the viewpoint of ensuring compatibility between the thermosetting resin and the thermoplastic resin, an acrylic resin is preferably used. Examples of the acrylic resin include a (meth)acrylic polymer as a polymer of a monomer component including a (meth)acrylic acid alkyl ester having a linear or branched alkyl group and another monomer (copolymerizable monomer).

[0038] The glass transition temperature (Tg) of the thermoplastic resin is preferably -70°C or higher. The glass transition temperature is preferably 0°C or lower, more preferably -5°C or lower. The glass transition temperature (Tg) of the polymer can be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of the polymer, Wi represents the weight fraction of the monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of the homopolymer can be determined by literature values. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999) and "New Polymer Library 7: Introduction to Synthetic Resins for Paints" (Kyozo Kitaoka, Polymer Publishing Association, 1995). On the other hand, the glass transition temperature of a homopolymer of a monomer can also be determined by the method specifically described in JP-A-2007-51271.

[0039] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]

[0040] The weight average molecular weight of the thermoplastic resin is preferably 100,000 or more, and more preferably 300,000 or more. The weight average molecular weight of the thermoplastic resin is preferably 2,000,000 or less, and more preferably 1,000,000 or less. The weight average molecular weight of the resin is measured by gel permeation chromatography (GPC) based on a standard polystyrene equivalent value.

[0041] The content of the thermoplastic resin in the thermosetting composition is preferably 1% by mass or more, more preferably 2% by mass or more, and is preferably 80% by mass or less, more preferably 60% by mass or less.

[0042] Examples of the pigment include black pigments such as carbon black. The particle size of the pigment is, for example, 0.001 μm or more, and, for example, 1 μm or less. The particle size of the pigment is an arithmetic mean diameter obtained by observing the pigment with an electron microscope. The content of the pigment in the thermosetting composition is, for example, 0.1 mass % or more, and, for example, 2 mass % or less.

[0043] Examples of the silane coupling agent include silane coupling agents containing an epoxy group. Examples of the silane coupling agent containing an epoxy group include 3-glycidoxydialkyldialkoxysilane and 3-glycidoxyalkyltrialkoxysilane. Examples of the 3-glycidoxydialkyldialkoxysilane include 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane. Examples of the 3-glycidoxyalkyltrialkoxysilane include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. As the silane coupling agent, 3-glycidoxyalkyltrialkoxysilane is preferably used, and more preferably 3-glycidoxypropyltrimethoxysilane is used. The content of the silane coupling agent in the thermosetting composition is preferably 0.1% by mass or more, more preferably 1% by mass or more. The content is preferably 10% by mass or less, more preferably 5% by mass or less.

[0044] The sealing resin sheet X can be produced, for example, as follows.

[0045] First, the components described above for the thermosetting composition are mixed with a solvent to prepare a varnish of the thermosetting composition. Examples of the solvent include methyl ethyl ketone, ethyl acetate, and toluene. The hollow ceramic filler has a hollow structure but is hard, so it is not easily crushed during mixing. In addition, the hollow ceramic filler has a smaller density per occupied volume and is lighter than a solid inorganic filler. Therefore, although the hollow ceramic filler is a bulky particle, it is easy to mix it appropriately with other components, and therefore it is easy to disperse it appropriately in the thermosetting composition.

[0046] Next, the varnish is applied onto a substrate such as a release film to form a coating film, and the coating film is then dried by heating. This allows a composition film of a predetermined thickness in a semi-cured state to be formed as an encapsulating resin sheet X (in FIG. 1, the encapsulating resin sheet X is disposed on a release film L shown by an imaginary line). Examples of the release film include flexible plastic films. Examples of the plastic film include polyethylene terephthalate films, polyethylene films, polypropylene films, and polyester films. The thickness of the release film is, for example, 3 μm or more and, for example, 200 μm or less. The surface of the release film is preferably release-treated.

[0047] When a thick encapsulating resin sheet X is produced, a plurality of composition films may be bonded together and integrated under heating conditions. The heating temperature is, for example, 70°C to 90°C.

[0048] In this manner, a encapsulating resin sheet X having a predetermined thickness can be produced. The thickness of the encapsulating resin sheet X is, for example, 10 μm or more, preferably 25 μm or more, and more preferably 30 μm or more. The thickness of the encapsulating resin sheet X is, for example, 3000 μm or less, preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 300 μm or less, and particularly preferably 100 μm or less.

[0049] The encapsulating resin sheet X has a viscosity at 90°C of preferably 100 kPa·s or more, more preferably 200 kPa·s or more, and further preferably 300 kPa·s or more. Such a configuration is preferable for ensuring the fluidity of the encapsulating resin sheet X in the pressing step described below. The viscosity of the encapsulating resin sheet X at 90°C is, for example, 1000 kPa·s or less. The viscosity at 90°C can be determined by a measurement method described later in the examples.

[0050] After the encapsulating resin sheet X is cured by heating at 150°C for 1 hour, the average linear thermal expansion coefficient at 30°C to 50°C is preferably 50 ppm / °C or less, more preferably 45 ppm / °C or less, and even more preferably 40 ppm / °C or less. Such a configuration is suitable for suppressing peeling from the semiconductor chip in the cured resin portion formed from the encapsulating resin sheet X, and is therefore preferable for ensuring encapsulation reliability. The average linear thermal expansion coefficient is, for example, 0 ppm / °C. The average linear thermal expansion coefficient can be determined by a measurement method described later in the examples.

[0051] The encapsulating resin sheet X has a tensile storage modulus at 25°C after being cured by heating at 150°C for 1 hour of preferably 1 GPa or more, more preferably 1.5 GPa or more, and even more preferably 1.8 GPa or more. Such a configuration is preferable for ensuring the strength of the cured resin part. The tensile storage modulus is, for example, 20 GPa or less. The tensile storage modulus can be measured by the method described later in the examples.

[0052] After the encapsulating resin sheet X is cured by heating at 150°C for 1 hour, the relative dielectric constant at 10 GHz is preferably 3.4 or less, more preferably 2.8 or less, and even more preferably 2.5 or less. Such a configuration is preferable for reducing the transmission loss of high-frequency signals passing through the cured resin part. The relative dielectric constant is, for example, 1 or more. The relative dielectric constant can be measured by the method described later in the examples.

[0053] FIG. 2 shows, as an example of a method of using the encapsulating resin sheet X, a method of encapsulating a semiconductor chip on a substrate using the encapsulating resin sheet X.

[0054] In this method, first, as shown in FIG. 2A, a workpiece W and a sealing resin sheet X are placed between a first press plate P1 and a second press plate P2 of a flat plate press (placement step).

[0055] The workpiece W includes a substrate 10 and a plurality of chips 20. The substrate 10 is a base material that is later divided into single mounting substrates, and has a mounting surface 11. The mounting surface 11 is provided with a terminal for mounting (not shown). The chip 20 is a semiconductor chip. In this embodiment, the semiconductor chip is a semiconductor chip for wireless communication. The operating frequency of the semiconductor chip is, for example, 0.01 to 100 GHz. The chip 20 also has a main surface 21 and a side surface 22. The main surface 21 is provided with a terminal for external connection (not shown). The chip 20 is mounted on the substrate 10 via bump electrodes 23 with the main surface 21 facing the substrate 10 across a gap G. Each bump electrode 23 is interposed between a terminal provided on the mounting surface 11 of the substrate 10 and a terminal provided on the main surface 21 of the chip 20, and electrically connects the substrate 10 and the chip 20. Moreover, the multiple chips 20 are arranged at intervals from one another in the planar direction on the mounting surface 11 of the substrate 10. The interval between adjacent chips 20 is, for example, 50 μm or more and, for example, 10 mm or less.

[0056] In this step, the work W is placed on the first press plate P1 so that the substrate 10 is in contact with the first press plate P1. The sealing resin sheet X is placed with respect to the work W so that the chip 20 of the work W is in contact with the substrate 10.

[0057] 2B, the encapsulating resin sheet X and the workpiece W are pressed in the thickness direction T by a first press plate P1 and a second press plate P2 (pressing step). Specifically, in a state in which the encapsulating resin sheet X contacts the chip 20 on the substrate 10, the encapsulating resin sheet X is softened by heating and pressed toward the substrate 10.

[0058] The pressing pressure is, for example, 0.01 MPa or more, and preferably 0.05 MPa or more. The pressing pressure is, for example, 10 MPa or less, and preferably 5 MPa or less. The pressing time is, for example, 0.3 minutes or more, and preferably 0.5 minutes or less. The pressing time is, for example, 10 minutes or more, and preferably 5 minutes or less. The heating temperature during pressing is, for example, 40°C or more, and preferably 60°C or more. The heating temperature is, for example, 100°C or less, and preferably 95°C or less.

[0059] In this process, the sealing resin sheet X, while maintaining the B stage, deforms in accordance with the outer shape of the chips 20, covers the side surfaces 22 of each chip 20, and comes into contact with the mounting surface 11 of the substrate 10 that does not overlap with the chips 20 in a plan view. As a result, the gap G between the substrate 10 and the chips 20 becomes a closed space.

[0060] Next, the workpiece W with the encapsulating resin sheet X is removed from the flat plate press, and then the encapsulating resin sheet X is heated and cured (curing step) as shown in Fig. 2C. This forms a cured resin portion 30 that encapsulates each chip 20 on the substrate 10.

[0061] The heating temperature (cure temperature) is, for example, 100° C. or higher, preferably 120° C. or higher. The heating temperature (cure temperature) is, for example, 200° C. or lower, preferably 180° C. or lower. The heating time is, for example, 10 minutes or longer, preferably 30 minutes or longer. The heating time is, for example, 180 minutes or shorter, preferably 120 minutes or shorter.

[0062] Thereafter, the cured resin portion 30 (cured sealing resin sheet X) and the substrate 10 are cut along predetermined cutting lines, for example, by blade dicing, to separate into individual semiconductor packages.

[0063] As described above, the sealing resin sheet X contains a hollow ceramic filler as an inorganic filler. A ceramic filler having a hollow structure has a smaller dielectric constant per occupied volume than a ceramic filler having a solid structure. In addition, the hollow ceramic filler is hard and is not easily crushed in the above-mentioned pressing process. The sealing resin sheet X containing such a hollow ceramic filler is suitable for effectively forming a cured resin portion 30 having a low dielectric constant while suppressing a decrease in the occupied volume of the hollow inorganic filler in the above-mentioned pressing process.

[0064] As described above, the sealing resin sheet X is suitable for collectively sealing a plurality of semiconductor chips with a cured resin portion having a low dielectric constant, and is therefore suitable for efficiently manufacturing a semiconductor package in which transmission loss in wireless communication is suppressed. EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amount (content), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "not more than" or "less than") or lower limit (a numerical value defined as "not less than" or "more than") of the corresponding blending amount (content), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0066] [Examples 1 to 4 and Comparative Example 1] Each component was mixed according to the formulation shown in Table 1 to prepare a varnish of the composition (in Table 1, the units of each numerical value expressing the composition are relative "parts by mass"). Next, the varnish was applied to a polyethylene terephthalate film (PET film) whose surface had been subjected to silicone release treatment to form a coating film. Next, this coating film was heated and dried at 110°C for 5 minutes to form a composition film having a thickness of 65 μm on the PET film (the formed composition film is in a B-stage state). Next, four sheets of the composition film were laminated together at 80°C to prepare a sealing resin sheet having a thickness of 260 μm (the formed sealing resin sheet is in a B-stage state).

[0067] Viscosity of Sealing Resin Sheet The viscosity at 90°C was measured for each of the encapsulating resin sheets of Examples 1 to 4 and Comparative Example 1. In this measurement, a rheometer (trade name "HAAKE MARS III", manufactured by Thermo Fisher Scientific) was used, and a sample taken from the encapsulating resin sheet was sandwiched between a heating plate in the device and a parallel plate (diameter 8 mm) arranged parallel to the heating plate, with a gap between the plates set to 1 mm. The viscosity was measured under the conditions of a frequency of 1 Hz, a strain value of 0.005%, a measurement temperature range of 50°C to 90°C, and a temperature rise rate of 30°C / min. Table 1 shows the viscosity (kPa·s) at 90°C.

[0068] <Average linear thermal expansion coefficient> The average linear thermal expansion coefficient after curing was examined for each of the encapsulating resin sheets of Examples 1 to 4 and Comparative Example 1 as follows. First, the encapsulating resin sheet was cured by heating at 150° C. for 1 hour. Next, a sample piece for measurement (width 4.5 mm×length 15 mm×thickness 260 μm) was cut out from the encapsulating resin sheet after curing. Next, the linear thermal expansion coefficient of the sample piece was measured by a thermomechanical measuring device (product name "TMA8310", manufactured by Rigaku Co., Ltd.). In this measurement, the measurement mode was set to tensile mode, the tensile load of the sample piece was set to 2 g, the measurement temperature range was set to 25° C. to 260° C., and the heating rate was set to 5° C. / min. Then, the average linear thermal expansion coefficient (ppm / ° C.) from 30° C. to 50° C. was obtained from the thermal expansion coefficient data at 0.1° C. intervals from 30° C. to 50° C. The values ​​are shown in Table 1.

[0069] Tensile storage modulus The tensile storage modulus after curing was measured for each of the encapsulating resin sheets of Examples 1 to 4 and Comparative Example 1 as follows. First, the encapsulating resin sheet was cured by heating at 150° C. for 1 hour. Next, a sample piece for measurement (width 10 mm×length 40 mm×thickness 260 μm) was cut out from the encapsulating resin sheet after curing. Next, the tensile storage modulus was measured in a temperature range of −10° C. to 260° C. using a dynamic viscoelasticity measuring device (product name “RSA-G2”, manufactured by TA Instruments). In this measurement, the initial chuck distance of the chuck for holding the sample piece was 22.5 mm, the measurement mode was the tension mode, the heating rate was 10° C. / min, the frequency was 1 Hz, and the dynamic strain was 0.05%. The tensile storage modulus (GPa) at 25° C. is shown in Table 1.

[0070] <Dielectric constant> For each of the encapsulating resin sheets of Examples 1 to 4 and Comparative Example 1, the dielectric constant at 10 GHz after curing was measured as follows. First, the encapsulating resin sheet was cured by heating at 150° C. for 1 hour. Next, a sample piece for measurement (width 30 mm×length 30 mm×thickness 260 μm) was cut out from the encapsulating resin sheet after curing. Next, the dielectric constant of the sample piece at 10 GHz was measured using a PNA network analyzer (manufactured by Agilent Technologies) and a split post dielectric resonator (SPDR). The measurement results are shown in Table 1.

[0071] [Table 1]

[0072] The components used in the examples and comparative examples are as follows. Epoxy resin: "YSLV-80XY" manufactured by Nippon Steel Chemical Co., Ltd. (bisphenol F type epoxy resin, high molecular weight epoxy resin, epoxy equivalent 191g / eq, solid at room temperature, softening point 80℃) Phenolic resin: Gun-ei Chemical's "LVR-8210DL" (novolac type phenolic resin, latent hardener, hydroxyl equivalent 104g / eq, solid at room temperature, softening point 60℃) Acrylic resin: "HME-2006M" manufactured by Negami Chemical Industries Co., Ltd. (acrylic resin containing carboxyl groups, acid value 32 mg KOH / g, weight average molecular weight 1.29 million, glass transition temperature (Tg) -13.9°C, methyl ethyl ketone solution with solid content concentration of 20% by mass) Hollow ceramic filler: "Cellspheres" manufactured by Taiheiyo Cement Corporation (aluminoborosilicate glass, hollow spherical particles, average particle diameter 4.0 μm, particle density 0.6 g / cm 3 ) First silica filler: "FB-8SM" manufactured by Denka Co., Ltd. (spherical silica particles, average particle size 7.0 μm, no surface treatment) Second silica filler: Admatechs' "SC220G-SMJ" (spherical silica particles, average particle size 0.5 μm) surface-treated with 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical's "KBM-503") (the silane coupling agent used for surface treatment was 1 part by mass per 100 parts by mass of silica particles). Curing accelerator: "2PHZ-PW" (2-phenyl-4,5-dihydroxymethylimidazole) manufactured by Shikoku Chemical Industry Co., Ltd. Silane coupling agent: Shin-Etsu Chemical's "KBM-403" (3-glycidoxypropyltrimethoxysilane) Pigment: Mitsubishi Chemical's "Carbon Black #20" (average particle size 50 nm) Solvent: Methyl ethyl ketone [Explanation of symbols]

[0073] X Sealing resin sheet T thickness direction W work 10 Substrate 11 Mounting surface 20 Chip 21 Main surface 22 Side 23 Bump electrode 30 Cured resin part P1 First press plate P2 Second press plate

Claims

1. A sealing resin sheet containing a thermosetting resin, an inorganic filler, and a thermoplastic resin, The sealing resin sheet, wherein the inorganic filler includes a hollow ceramic filler.

2. The sealing resin sheet according to claim 1 , wherein a content ratio of the hollow ceramic filler is 50% by volume or more.

3. 3. The sealing resin sheet according to claim 1, wherein a content ratio of the hollow ceramic filler is 85 volume % or less.

4. The encapsulating resin sheet according to any one of claims 1 to 3, having an average linear thermal expansion coefficient of 50 ppm / °C or less at 30°C to 50°C after curing.

5. The encapsulating resin sheet according to claim 1 , which has a tensile storage modulus at 25° C. after curing of 1 GPa or more.

6. The encapsulating resin sheet according to claim 1 , which has a relative dielectric constant of 3.4 or less at 10 GHz after curing.

Citation Information

Patent Citations

  • Semiconductor device

    JP1990082644A

  • Resin composition and its manufacture

    JP1993009270A

  • Acrylic sheet, acrylic bonding sheet and their production

    JP1996053597A

  • Production of acrylic sheet and acrylic adhesive sheet

    JP1996157616A

  • Epoxy resin composition for semiconductor sealing and semiconductor device using the same

    JP2001354754A